Effects of temperature and salinity on the development and survival of the embryos and zoeae i from the southern surf crab Ovalipes trimaculatus (Brachyura: Portunidae) - Martelli, Antonela (2021)
Ovalipes trimaculatus is a highly valued fisheries resource with high potential for aquaculture production. Still, there is need for experimental information to sustain efficient husbandry practices. In this work we analyze the combined effects of different thermo-haline conditions on the length of development and survival of embryos (6, 10, 13, 15, 18, 22, 24 ⁰C x 30, 33 ‰; 13 ⁰C x 26, 30, 33, 37 ‰) and zoeae I (13, 18, 22 ⁰C x 30, 33 ‰; 13 ⁰C x 26, 30, 33, 37 ‰) from individuals sampled in the Atlantic coast of Patagonian. Among the most relevant results, it was found that the mean length of embryogenesis decreased from 63 to 19 days with increasing temperatures, but was not affected by seawater salinity. Mean embryonic survival was significantly lower at the combination of the highest temperature and salinity tested. Also, it differed between salinity conditions. Both at 30 and 33‰, the length of the Zoea I stage significantly varied between thermal treatments, being significantly longer at 13⁰C. No zoeae I reared at 13 ⁰C survived at 37‰ and mean survival at 26‰ halved that of 30-33‰. Results obtained reduce aquaculture production costs.